2020
DOI: 10.3389/fchem.2020.551710
|View full text |Cite
|
Sign up to set email alerts
|

Efficiencies Evaluation of Photocatalytic Paints Under Indoor and Outdoor Air Conditions

Abstract: The removal of indoor and outdoor air pollutants is crucial to prevent environmental and health issues. Photocatalytic building materials are an energy-sustainable technology that can completely oxidize pollutants, improving in situ the air quality of contaminated sites. In this work, different photoactive TiO 2 catalysts (anatase or modified anatase) and amounts were used to formulate photocatalytic paints in replacement of the normally used TiO 2 (rutile) pigment. These paints were tested in two different ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The outdoor experiments under UV light showed that the conversion ability of the different paints all decreased substantially with time, possibly due to oxidation products forming on the surfaces. 124 , 125 …”
Section: Toward Visible-light Activity–dopingmentioning
confidence: 99%
See 2 more Smart Citations
“…The outdoor experiments under UV light showed that the conversion ability of the different paints all decreased substantially with time, possibly due to oxidation products forming on the surfaces. 124 , 125 …”
Section: Toward Visible-light Activity–dopingmentioning
confidence: 99%
“…The outdoor experiments under UV light showed that the conversion ability of the different paints all decreased substantially with time, possibly due to oxidation products forming on the surfaces. 124,125 Currently, most commercial self-cleaning window surface coatings can only be activated by UV light. Recently, Peeters et al manufactured a transparent photocatalytic self-cleaning Au/TiO 2 coating that is activated in normal light conditions.…”
Section: Dopants In Coatings and Paintsmentioning
confidence: 99%
See 1 more Smart Citation
“…showing that titanium(IV) oxide is active against gram-positive and gram-negative bacteria ( Lactobacillus acidophilus and Escherichia coli , respectively) and yeast Saccharomyces cerevisiae [ 20 ]. The main area of photocatalysis application is the preparation of self-cleaning surfaces (also for antifouling purposes) [ 21 , 22 , 23 , 24 , 25 ]. However, more and more interest has recently been focused on indoor air purification [ 26 ], water/wastewater treatment [ 27 ], fabrication of masks and clothes [ 28 ], and medical purposes (wound healing [ 29 , 30 ]).…”
Section: Applications Of Photocatalysis Against Co-pathogens Of Covid...mentioning
confidence: 99%
“…With the aim of developing titanium-based photoactive coatings under visible light, some research works have focused on reducing the band gap of these materials. Some of the strategies employed are based on doping titanium dioxide with other metals, such as silver, 10 aluminum, 11 tin, 12 iron and zinc, 13 or with non-metals, such as carbon, 14 nitrogen 15,16 and mixtures of silicon-nitrogen. 17 Some other research works have focused on developing photoactive coatings with low processing temperatures by doping amorphous titanium(IV) oxide with nickel and nitrogen.…”
Section: Introductionmentioning
confidence: 99%